Critical Review of Private Limited Liability Hospitals in the Perspective of Article 34 Paragraph (3) of the 1945 Constitution - Hasrul Buamona; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Fulfillment of health one of which is the provision of hospitals which is the responsibility of the government, which cannot be transferred to the private sector like a Limited Liability Company. This has been clearly regulated in Article 34 paragraph (3) of the 1945 Constitution. This then became the background and also became the main focus of the study entitled